(untitled) (Colombia Medica, 2023)
Fragile X syndrome is caused by the expansion of CGG triplets in the FMR1 gene, which generates epigenetic changes that silence its expression. The absence of the protein coded by this gene, FMRP, causes cellular dysfunction, leading to impaired brain development and functional abnormalities. The physical and neurologic manifestations of the disease appear early in life and may suggest the diagnosis. However, it must be confirmed by molecular tests. It affects multiple areas of daily living and greatly burdens the affected individuals and their families. Fragile X syndrome is the most common monogenic cause of intellectual disability and autism spectrum disorder; the diagnosis should be suspected in every patient with neurodevelopmental delay. Early interventions could improve the functional prognosis of patients with Fragile X syndrome, significantly impacting their quality of life and daily functioning. Therefore, healthcare for children with Fragile X syndrome should include a multidisciplinary approach.